Distinguishing syn-cleavage folds from pre-cleavage folds to which cleavage is virtually axial planar: examples from the Cambrian core of the Lower Palaeozoic Anglo-Brabant Deformation Belt (Belgium) - Debacker, T.; Van Noorden, Michiel; Sintubin, Manuel (Journal of Structural Geology, 2006)
Within the Cambrian Jodoigne Formation in the easternmost part of the Anglo-Brabant Deformation Belt, sub-horizontal to gently plunging folds occur within the limbs of steeply plunging folds. The latter folds are cogenetic with cleavage and are attributed to the Brabantian deformation event. In contrast, although cleavage is also (1) virtually axial planar to the sub-horizontal to gently plunging higher-order folds, shows (2) a well-developed divergent fanning across these folds, (3) an opposing sense of cleavage refraction on opposite fold limbs, and (4) only very small cleavage transection angles, an analysis of the cleavage/bedding intersection lineation suggests that these higher-order folds have a pre-cleavage origin. On the basis of a comparison of structural and sedimentological features these higher-order folds are interpreted as slump folds. The seemingly 'normal' cleavage/fold relationship across the slump folds within the limbs of the large steeply plunging folds is due to the very small angle between cleavage and bedding. As such, a 'normal' cleavage/fold relationship is no guarantee for a syn-cleavage fold origin. It is not unlikely that also within undeformed, recumbent slump folds, a well-developed compaction fabric, formed parallel to the axial surface of the slump folds, may show fanning and contrasting senses of cleavage refraction on opposite fold limbs. © 2006 Elsevier Ltd. All rights reserved. status: Published